Poverty and income maintenance in old age: A cross-national view of low income older women - Timothy M. Smeeding; Susanna Sandstrom (Luxembourg Income Study (LIS), 2005)
Great strides have been made in reducing poverty amongst the elderly in most rich countries over the past forty years. But pensioner poverty has not been eradicated, especially in the English-speaking nations. Poverty rates amongst older women are much higher than those for older men and much higher in the United States compared to other nations. In general, poverty rates rise with both age and changes in living arrangements though living alone has a larger effect for women. Poverty rates among older women are highest amongst the divorced, widowed and never- married, groups whose prevalence within the elder population will rise significantly over the next decades. The challenge for policy makers is to design systems of retirement benefits that guarantee minimum standards of living for all elderly women while also preserving incentives for self-financed retirement.
Keywords: 330; Einkommen; Armut; Öffentliche Sozialleistungen; Gesetzliche Rentenversicherung; Alte Menschen; Frauen; Vergleich; Deutschland; Italien; Finnland; Kanada; Schweden; Großbritannien; USA